Ferrostalderite, CuFe2TlAs2S6, a new mineral from Lengenbach, Switzerland: occurrence, crystal structure, and emphasis on the role of iron in sulfosalts. (1st February 2016) - Biagioni, Cristian; Bindi, Luca; Nestola, Fabrizio; Cannon, Ralph; Roth, Philippe; Raber, Thomas
The new mineral species ferrostalderite, CuFe2TlAs2S6, was discovered in the Lengenbach quarry, Binn Valley, Wallis, Switzerland. It occurs as minute, metallic, black, equant to prismatic crystals, up to 50 mu;m, associated with dolomite, realgar, baumhauerite (?) and pyrite. Minimum and maximum reflectance data for COM wavelengths in air are [λ (nm): R (%)]: 471.1: 24.2/25.4; 548.3: 23.7/24.7; 586.6: 22.9/23.8; 652.3: 21.0/22.0. Electron microprobe analyses give (wt.%): Cu 6.24(25), Ag 4.18(9), Fe 9.95(83), Zn 4.46(91), Hg 1.22(26), Tl 26.86(62), As 19.05(18), Sb 0.63(6), S 25.39(47), total 97.98(72). On the basis of 12 atoms per formula unit, the chemical formula of ferrostalderite is Cu0.75(2)Ag0.30(1)Fe1.36(10) Zn0.52(11) Hg0.05(1) Tl1.00(1)[As1.94(4)Sb0.04(1)]∑1.98(4)S6.04(4). The new mineral is tetragonal, space group I42 m, with a = 9.8786(5), c = 10.8489(8) Å, V = 1058.71(11) Å3, Z = 4. The main diffraction lines of the calculated powder diagram are [d (in Å), intensity, hkl]: 4.092, 70, 211; 3.493, 23, 220; 3.396, 35, 103; 3.124, 17, 310; 2.937, 100, 222; 2.656, 19, 321; 2.470, 19, 400; 2.435, 33, 303. The crystal structure of ferrostalderite has been refined by Xray single-crystal data to a final R1 = 0.050, on the basis of 1169 reflections with F0 > 4σ(F0). It shows a three dimensional framework of (Cu, Fe)-centred tetrahedra (1M1 + 2 M2), with channels parallel to [001] hosting disymmetric TlS6 and (As, Sb)S3 polyhedra. Ferrostalderite is derived from its isotype stalderite M1CuM2Zn2TlAs2S6 through the homovalent substitution M2Zn2+ → M2Fe2+. The ideal crystal-chemical formula of ferrostalderite is M1CuM2Fe2TlAs2S6.